2015
DOI: 10.15345/iojes.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Do School Experiences Predict Life Satisfaction in Turkish College Students?

Abstract: The aim of this research is to examine the predictive role of school experiences on life satisfaction. Participants were 311 college students. In this study, the Perceived School Experiences Scale and the Satisfaction with Life Scale were used. The relationships between school experiences and life satisfaction were examined using correlation analysis and multiple regression analysis. In correlation analysis, academic press, academic motivation, and school connectedness were found positively related to life sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 65 publications
1
4
0
2
Order By: Relevance
“…Pozitif okul yaşantıları mutluluğu olumlu şekilde etkilemektedir (Akın, 2015;Gilman ve Huebner, 2006;Stiglbauer, Gnambs, Gamsjäger ve Batinic, 2013). Örneğin, iyimserlik sağlıklı davranışları ortaya çıkararak, aktif başa çıkmayı geliştirerek ve stresin etkilerinden koruyarak ergenlerin iyi oluşuna katkıda bulunmaktadır (Ben-Zur, 2003).…”
Section: Tartışma Sonuç Ve öNerilerunclassified
See 1 more Smart Citation
“…Pozitif okul yaşantıları mutluluğu olumlu şekilde etkilemektedir (Akın, 2015;Gilman ve Huebner, 2006;Stiglbauer, Gnambs, Gamsjäger ve Batinic, 2013). Örneğin, iyimserlik sağlıklı davranışları ortaya çıkararak, aktif başa çıkmayı geliştirerek ve stresin etkilerinden koruyarak ergenlerin iyi oluşuna katkıda bulunmaktadır (Ben-Zur, 2003).…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Pozitif psikoloji alanındaki gelişmeler ile birlikte ulusal ve uluslararası literatürde mutluluk ile ilgili çalışmaların artış gösterdiği gözlenmektedir. Türkiye'de mutluluk ile ilgili araştırmalar incelendiğinde daha çok yetişkinler (Eryılmaz, 2014;Eryılmaz, 2015b), üniversite öğrencileri (Akın, 2015;Doğan ve Eryılmaz, 2013;İlhan ve Özbay, 2010;Sapmaz ve Doğan, 2012;Özbay, Palancı, Kandemir ve Çakır, 2012;Tuzgöl-Dost, 2007) ve lise öğrencilerine (Doğan ve Çelik, 2014;Eryılmaz, 2015a;Eryılmaz ve Atak, 2011;Eryılmaz ve Öğülmüş, 2010) yönelik olduğu görülmektedir. Üniversite ve lise öğrencilerinin mutluluklarını etkileyen faktörler ile ilgili birçok araştırma yapılmasına rağmen ortaokul yıllarında öğrencilerin mutluluğunu etkileyen faktörler ile ilgili sınırlı sayıda araş tırmanın olduğu görülmektedir (Bender, 1997).…”
Section: Introductionunclassified
“…While the roles of the school environment for students are to build healthy relationships with peers, develop their social skills, continue school attendance, succeed in the classroom, their efforts to graduate, protect their mental health; all of this makes up the content of the concept of "school experiences" (Anderson-Butcher, Amorose, Iachini, & Ball, 2012). School experiences have important implications for how students perceive themselves, their thoughts and feelings, and school life (Akın, 2015).Early adolescence (middle school period) is a difficult and sensitive period in psychological, social and academic changes. During the transition from primary school to secondary school, great changes occur in school experiences, and students are expected to adapt to these situations; at the same time, they must cope with negative situations that may occur during this developmental transition period (Goldstein, Boxer, & Rudolph, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The term of perceived school experience was conceptualized by Butcher, Amorose, Iachini & Ball (2012) by gathering the concepts of school commitment, academic motivation and academic pressure in the literature under one umbrella term, and it has found an area of application in Turkish literature with the studies of Akın and Sarıçam (2014). Studies on perceived school experiences (Akın, 2015;Baytemir, 2019;Baytemir, Kösterelioğlu, & Kösterelioğlu, 2015;Güler, 2019;Özkara & Kalkavan, 2018) are found in the literature. Jowett and Nezlek (2011) reported that the coach-athlete relationship is effective in the life satisfaction of the athletes, and contentment between the two increases the duration and quality of the relationship.…”
Section: Introductionmentioning
confidence: 99%